Subject English as citizenship education - Belas, Oliver; Hopkins, Neil (British educational research journal, 2019)
This article is equal parts educational history and political philosophy. We aim to remind readers that subject English (SE) and indeed state education emerge from the contradictory impulses of classical liberalism, and that, more than simply resembling citizenship education, SE emerges in the first instance as a form of highly normativising citizenship education. We further argue that, following England's recent educational reforms initiated by former Education Secretary Michael Gove, SE continues to be framed in moral terms consistent with citizenship education—again, of a highly normativising sort. England's current educational policy generally, and specifically the framing of SE, employs the language of liberal possibility, while ultimately espousing an invidious exclusionary and assimilationist politics. The framing of SE, moreover, is one that misrepresents the supposedly ‘rich and varied literary heritage’ it is supposed to exemplify and promote. The current political landscape in which the study of literature takes place is one where a crisis of liberalism is manifest (in terms of populism, radicalisation or apathy). However, we do not believe the answer is to retreat into a sealed, hermetic canon that excludes the reality that England and English literature are fundamentally multicultural and polyethnic. SE will be the poorer for not fully acknowledging and embodying this, for not enabling students to imaginatively and critically engage with characters and experiences that reflect both the present and long‐standing diversity of English society, as well as its present and long‐standing inequalities.